Ambulatory Management of Heavy Menstrual Bleeding - Di Spiezio Sardo, Attilio (Womens Health (Lond), 2016)
Heavy menstrual bleeding (HMB) has significant adverse effects on the quality of life of many women, placing an economic burden on both health services and society at large. Thus, it is essential that all women with HMB have easy access to the proper diagnostic and therapeutic work-up in an outpatient fashion, avoiding the more time-consuming inpatient management. This new outpatient approach for HMB is one of the latest development of gynecological practice and can offer both diagnostic and therapeutic procedures. This manuscript aims to show the current possibilities of the modern management of HMB, which can be safely and effectively accomplished in the outpatient setting: global and directed endometrial biopsy, levonorgestrel intrauterine system insertion as well as minimally invasive surgical procedures (encompassing a variety of operative hysteroscopic procedures and second-generation endometrial ablation) are described below.